Overview of the world food situation: Food security -- new risks and new opportunities - von Braun, Joachim; Bos, Maria Soledad; Brown, Mary Ashby; Cline, Sarah A.; Cohen, Marc J.; Pandya-Lorch, Rajul; Rosegrant, Mark W. (International Food Policy Research Institute, 2003)
Brief prepared for the Annual General Meeting of the Consultative Group on International Agricultural Research, Nairobi, October 29, 2003